A Comparative Analysis of Elitist and Public Opinion Evaluation of National Health Insurance Policy Performance - I-chun, Liu; Chii-ching, Chen (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This study discusses evaluation of National Health Insurance policy, using the policy Delphi method to obtain elite opinion on evaluation indicators of the policy and a telephone survey to collect general public opinion. Results indicated that the elite and the general public share a consensus on policy performance. The findings suggest that evaluations of NHI policy that incorporate elite and general public assessments may be preferable to evaluations based on assessments from just one sector of the population. Moreover, performance assessment should integrate the opinions of different representative sections of the population, as well as professional and democratic principles of decision-making. The study also provides evidence that public opinion and elite evaluation are correlated and shows considerable consistency in the evaluation of NHI policy regardless of the policy knowledge of the evaluators.